2016
DOI: 10.21451/1984-3143-ar863
|View full text |Cite
|
Sign up to set email alerts
|

Role of the oviduct and oviduct-derived products in ruminant embryo development

Abstract: The fact that embryos can be obtained in vitro undermines the role of the oviduct. However, it has been demonstrated that when in vitro produced bovine zygotes are cultured in the oviduct of sheep, cattle or mice the embryo quality is improved compared to the embryos produced in vitro. Thus the oviduct is not simply a passive organ required only for transporting the embryo to the uterus but also provides a suitable microenvironment for the early embryo. The study of physiological mechanisms and interactions be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 92 publications
(46 reference statements)
0
5
0
1
Order By: Relevance
“…Through Panther classification system and GO, glycodelin was identified to have catalytic activity and is associated with a role in cellular and metabolic processes. Studies have shown that glycodelin is synthesized in the endometrium (Seppälä et al, 2002;Spencer et al, 2004) as well as the luteinized granulosa cells of the ovary and is present in follicular fluid (Glister et al, 2014;Rizos et al, 2016). The timely expression of glycodelin during reproduction, in particular fertilization and implantation, is regulated by the endocrine system (Seppälä et al, 1997;Taheripanah et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Through Panther classification system and GO, glycodelin was identified to have catalytic activity and is associated with a role in cellular and metabolic processes. Studies have shown that glycodelin is synthesized in the endometrium (Seppälä et al, 2002;Spencer et al, 2004) as well as the luteinized granulosa cells of the ovary and is present in follicular fluid (Glister et al, 2014;Rizos et al, 2016). The timely expression of glycodelin during reproduction, in particular fertilization and implantation, is regulated by the endocrine system (Seppälä et al, 1997;Taheripanah et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian oocytes are fertilized in the oviduct and are developed while traveling inside the fallopian tube toward the uterus. Oviduct fluid is the environment first experienced by oocytes and actively regulates fertilization and subsequent preimplantation development (Rizos et al 2016, Pérez-Cerezales et al 2017. Chemical composition of oviduct fluids contains a variety of molecules including simple and complex carbohydrates, inorganic ions, lipids, phospholipids lactate, pyruvate, glucose, proteins and free amino acids (Leese et al 2001, Avilés et al 2010, Rizos et al 2016, Pérez-Cerezales et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Oviduct fluid is the environment first experienced by oocytes and actively regulates fertilization and subsequent preimplantation development (Rizos et al 2016, Pérez-Cerezales et al 2017. Chemical composition of oviduct fluids contains a variety of molecules including simple and complex carbohydrates, inorganic ions, lipids, phospholipids lactate, pyruvate, glucose, proteins and free amino acids (Leese et al 2001, Avilés et al 2010, Rizos et al 2016, Pérez-Cerezales et al 2017. Among the amino acids found in oviduct fluid, the non-essential amino acid glycine is one of the most abundant amino acids reaching up to few millimolar levels in many mammalian species, including bovine (Hugentobler et al 2007), rabbits (Leese et al 1979, Miller & Schultz 1987, and rats (Nakamura et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the molecular communication that occurs between the developing conceptus (embryo and associated extraembryonic membranes) and the maternal endometrium is key to enhancing our understanding of early pregnancy loss in cattle. During early pregnancy, the embryo induces very localised changes at the transcriptional level in the oviduct [1,2] and in vitro coculture of embryos with oviductal cells accelerates blastocyst development and changes the epigenetic status of the embryos [2,3]. This indicates that interaction with the female reproductive tract, while not strictly necessary for early embryo development, enhances embryo quality [4].…”
Section: Introductionmentioning
confidence: 99%